PENGARUH KUALITAS PRODUK, PROMOSI DAN KEBUTUHAN MENCARI VARIASI TERHADAP PERILAKU PERALIHAN MEREK (BRAND SWITCHING) PRODUK KOSMETIK SARIAYU DI KOTA PADANG - Atika Zahari; Susi Evanita (Jurnal Ecogen, 2018)
This study aims to examine the effect of quality of products, promotion and variety seeking towardbrand switchingSariayu cosmetic products in Padang. This research isdescriptive and qualitative research.. The population in this study was Padang city women who had used Sariayu cosmetic products. The sampling technique used is Purposive sampling with a total sample of 100 respondents.The type of data used is primary and secondary data. Thedata analysis technique used is multiple regression by using t test and F test. The analytical method used is path analysis using the SPSS version 21 program.The result of the research shows thatthere is a positive and insignificant influence between quality of products variables on brand switching behavior ofSariayu cosmetic products in Padang.Promotionvariableshas a positive and insignificant  effect to brand switching behavior ofSariayu cosmetic products in Padang. Then Variety Seeking variableshas a positive and insignificant  effect to brand switching behavior ofSariayu cosmetic products in Padang. Keyword: Quality of products, Promotion, Variety Seeking, Brand Switching